Coordination skills development of mogul skiers at the initial and preliminary stages of basic training - Naumchuk, V.; Grabyk, N.; Omelyanenko, I.; Omelyanenko, V.; Hrubar, I. (International Journal of Applied Exercise Physiology, 2020)
Purpose: The research is devoted to the problem of coordination skills development of mogul skiers. The purpose of the study is to develop a scientifically grounded program for the development of coordination skills of mogul skiers at the stages of initial and preliminary basic training. Results: The results of the study of coordination skills of mogul skiers depending on their gender, age, sports qualification, training experience and the stage of sports training have been analyzed. The structure of coordination skills of mogul skiers is determined. The program of coordination skills development of mogul skiers at the stages of initial and preliminary basic training, which involves the use of means of general and special coordination skill improvements, methods and methodical techniques as well as ideomotor, sensory motor and motor components of the mechanism of coordination skills has been proposed. Conclusion: The program of coordination skills development of mogul skiers at the stages of initial and preliminary basic training is substantiated. The factor structure of coordinating skills of mogul skiers is defined; the correlation relations between the results in sport of skilled mogul skiers and test scores for assessing the coordination abilities is shown; the lack of sexual differences in the coordination skills development of mogul skiers is determined.